Genotype-phenotype correlation in patients with 21-hydroxylase deficiency - Tang, Peng; Zhang, Jun; Peng, Song; Wang, Yapeng; Li, Haoyang; Wang, Ze; Zhang, Yao; Huang, Yiqiang; Xu, Jing; Zhang, Dianzheng; Liu, Qiuli; Wang, Luofu; et al. (Frontiers in Endocrinology, 2023)
21-hydroxylase deficiency (21OHD) is the most common cause of congenital adrenal hyperplasia (CAH). However, patients with 21OHD manifest various phenotypes due to a wide-spectrum residual enzyme activity of different CYP21A2 mutations. A total of 15 individuals from three unrelated families were included in this study. Target Capture-Based Deep Sequencing and Restriction Fragment Length Polymorphism was conducted on peripheral blood DNA of the three probands to identify potential mutations/deletions in CYP21A2; Sanger sequencing was conducted with the DNA from the family members of the probands. Dramatically different phenotypes were seen in the three probands of CAH with different compound heterozygous mutations in CYP21A2. Proband 1 manifested simple virilizing with mutations of 30-kb deletion/c.[188A>T;518T>A], the latter is a novel double mutants classified as SV associated mutation. Although both probands carry the same compound mutations [293-13C>G]:[518T>A], gonadal dysfunction and giant bilateral adrenal myelolipoma were diagnosed for proband 2 and proband 3, respectively. In conclusion, both gender and mutations contribute to the phenotypes, and patients with the same compound mutations and gender could present with different phenotypes. Genetic analysis could help the etiologic diagnosis, especially for atypical 21OHD patients.